Evaluasi Pengelolaan Limbah Medis Padat di Rumah Sakit Universitas Andalas - Dewi Fortuna Khairil; Nurhasan Syah; Eri Barlian; Nasfryzal Carlo (Jurnal Penelitian Pendidikan IPA, 2024)
Medical solid waste management still faces obstacles several problems such as the lack of use of complete personal protective equipment (PPE) by officers and the absence of special routes for transporting waste. This study aims to evaluate medical solid waste management in hospitals. The method used was qualitative with a purposive sampling technique of 10 informants at the location concerned. Data was collected through in-depth interviews, field observations, and document review, then processed and analyzed using a triangulation table of sources and methods. Even though hospitals have SOPs that are socialized to staff, adequate human resources, funds, facilities and infrastructure, not all of them meet the requirements. The waste reduction process has not been implemented, TPHS B3 has been used as a rest area for officers, the sulo has not been closed because medical waste is buried in non-medical waste, and there is no waste transportation route available. The research results show that the management of medical and non-medical waste is not fully in accordance with applicable regulations. Therefore, it is recommended that hospitals reduce waste, monitor waste officers, and provide special routes for transporting waste in accordance with applicable regulations